KINETICS OF PALM OIL TRANSESTERIFICATION IN METHANOL WITH POTASSIUM HYDROXIDE AS A CATALYST - Yoeswono Yoeswono; Triyono Triyono; Iqmal Tahir (Universitas Gadjah Mada, 2008)
A study on palm oil transesterification to evaluate the effect of some parameters in the reaction on the reaction kinetics has been carried out. Transesterification was started by preparing potassium methoxide from potassium hydroxide and methanol and then mixed it with the palm oil. An aliquot was taken at certain time interval during transesterification and poured into test tube filled with distilled water to stop the reaction immediately. The oil phase that separated from the glycerol phase by centrifugation was analyzed by 1H-NMR spectrometer to determine the percentage of methyl ester conversion. Temperature and catalyst concentration were varied in order to determine the reaction rate constants, activation energies, pre-exponential factors, and effective collisions. The results showed that palm oil transesterification in methanol with 0.5 and 1 % w/w KOH/palm oil catalyst concentration appeared to follow pseudo-first order reaction. The rate constants increase with temperature. After 13 min of reaction, More methyl esters were formed using KOH 1 % than using 0.5 % w/w KOH/palm oil catalyst concentration. The activation energy (Ea) and pre-exponential factor (A) for reaction using 1 % w/w KOH was lower than those using 0.5 % w/w KOH.